Aortic Rupture during Endovascular Aneurysm Repair. Report of Our Experience and Review of the Literature - Moulakakis, Konstantinos G.; Lazaris, Andreas M.; Kakisis, John D.; Sfyroeras, George S.; Theocharopoulos, George; Panagiotopoulos, Andreas I.; Krinos, Nikolas; Geroulakos, George (AORTA, 2020)
Background Aortic neck wall rupture during endovascular repair of abdominal aortic aneurysms (EVAR) is an underreported potentially fatal complication. Only a few cases have been reported. The main cause of this complication is repeated attempts at balloon inflation or overdilation to treat an intraoperative Type 1a endoleak. We report three cases complicated by procedure-related aortic neck wall rupture during EVAR. We also review the literature regarding the causes and outcomes of this complication.Methods Medical records of all patients undergoing EVAR between January 2009 and March 2019 were retrospectively reviewed.Results Overall, 824 EVAR procedures were performed, and rupture of the aortic neck wall was observed in three patients. In all cases, a Type 1a endoleak was observed and, in all cases, repeated ballooning attempts had been performed to resolve the endoleaks. In all cases, conversion to open repair was performed and all patients survived.Conclusion In cases of Type 1a endoleak, a maximum of two ballooning attempts should be performed even if a Type 1a endoleak persists. In case of intraoperative aortic neck wall rupture, control of the hemorrhage should be achieved immediately by advancing the balloon above the site of rupture. Emergency surgical conversion in case of hemodynamic stability is the first choice. According to the literature, emergency surgical conversion, especially in cases of endograft with suprarenal fixation, is associated with significant morbidity and mortality rates, mainly due to hemorrhage and to the length of the procedure required to repair the aortic neck wall injury.
Keywords: EVAR; intraoperative; aortic rupture; open conversion; acute conversion